Pathogenesis and management of high molecular risk myeloproliferative neoplasms - Victoria Y. Ling; Florian H. Heidel; Megan J. Bywater (Haematologica)
Classical myeloproliferative neoplasms (MPNs) are clonal stem cell disorders characterised by driver mutations that affect the constitutive activation of JAK-signalling. Additional mutations to an MPN-driver occur in a large number of patients and have been shown be associated with disease presentation and progression. In this review, we will outline the current hypotheses regarding how clonal evolution in MPN is thought to occur and the functional mechanisms as to how concomitant somatic mutations (i.e. mutations in genes other than the ‘driver’ genes) contribute to disease progression. We will discuss the definitions of high molecular risk MPN, provide an overview as to how concomitant mutations influence the clinical management of MPN and suggest how this rapidly developing genetic risk stratification can be utilised to improve clinical outcomes.